MARTX effector cross kingdom activation by Golgi‐associated ADP‐ribosylation factors. (19th February 2016) - Kim, Byoung Sik; Satchell, Karla J. F.
Summary: Vibrio vulnificus infects humans and causes lethal septicemia. The primary virulence factor is a multifunctional‐autoprocessing repeats‐in‐toxin (MARTX) toxin consisting of conserved repeats‐containing regions and various effector domains. Recent genomic analyses for the newly emerged V . vulnificus biotype 3 strain revealed that its MARTX toxin has two previously unknown effector domains. Herein, we characterized one of these domains, Domain X (DmXVv ). A structure‐based homology search revealed that DmXVv belongs to the C58B cysteine peptidase subfamily. When ectopically expressed in cells, DmXVv was autoprocessed and induced cytopathicity including Golgi dispersion. When the catalytic cysteine or the region flanking the scissile bond was mutated, both autoprocessing and cytopathicity were significantly reduced indicating that DmXVv cytopathicity is activated by amino‐terminal autoprocessing. Consistent with this, host cell protein export was affected by Vibrio cells producing a toxin with wild‐type, but not catalytically inactive, DmXVv . DmXVv was found to localize to Golgi and to directly interact with Golgi‐associated ADP‐ribosylation factors ARF1, ARF3 and ARF4, although ARF binding was not necessary for the subcellular localization. Rather, this interaction was found to induce autoprocessing of DmXVv . These data demonstrate that the V . vulnificus hijacks the host ARF proteins to activate the cytopathic DmXVv effector domain of MARTX toxin.